Modeling the situation awareness by the analysis of cognitive process - Liu, Shuang; Wanyan, Xiaoru; Zhuang, Damin (Bio-medical materials and engineering, 2014)
To predict changes of situation awareness (SA) for pilot operating with different display interfaces and tasks, a qualitative analysis and quantitative calculation joint SA model was proposed. Based on the situational awareness model according to the attention allocation built previously, the pilot cognitive process for the situation elements was analyzed according to the ACT-R (Adaptive Control of Thought, Rational) theory, which explained how the SA was produced. To verify the validity of this model, 28 subjects performed an instrument supervision task under different experiment conditions. Situation Awareness Global Assessment Technique (SAGAT), 10-dimensional Situational Awareness Rating Technique (10-D SART), performance measure and eye movement measure were adopted for evaluating SAs under different conditions. Statistical analysis demonstrated that the changing trend of SA calculated by this model was highly correlated with the experimental results. Therefore the situational awareness model can provide a reference for designing new cockpit display interfaces and help reducing human errors.